FEATURES OF THE SYSTEM OF COMMUNICATION IN THE ORGANIZATION OF PROBLEM EDUCATIONAL CLASSES - Mamatkulov Abdurashid Vaxidovich; Avlaev Orif Avlaevich (Web of Journals Publishing, 2023)
This article discusses the features of the organization of problem-based learning in the educational process and the importance of the communicative system in problem-based learning.
Keywords: pedagogical technologies, problem-based learning, thinking, communication system, independent thinking.